CRITICISM OF THE CONCEPT OF INTERTEKSTUALITY OF THE QURAN WITH JEWISH TRADITION IN ABRAHAM GEIGER'S VIEW - As’adah, Rifqi (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
The main focus of this research is the thoughts of Abraham Geiger regarding the Al-Qur'an and Prophet Muhammad SAW. Abraham Geiger is an orientalist who has a skeptical attitude and gives a negative assessment of Prophet Muhammad SAW. Through his monumental work entitled "Wat hat Mohammad aus dem judentume Aufgenommen", Geiger tries to prove the existence of Jewish influence in the Al-Qur'an adopted by Prophet Muhammad SAW. The researcher uses library research and hermeneutic analysis to analyze the data. The results of this study show that Geiger appears to give a negative assessment of the figure of Prophet Muhammad SAW and believes that the Al-Qur'an is influenced by Jewish tradition. However, critical analysis shows that it is not possible for Prophet Muhammad to adopt Jewish teachings due to his relatively short interaction with some Jewish figures. In addition, the Al-Qur'an also consists of various fields of knowledge that exist before and after the Al-Qur'an was revealed. This shows that the Al-Qur'an gives high appreciation to previous sacred books and also confirms that the Al-Qur'an is not only influenced by Jewish tradition, but also by other religious languages. However, despite this, Abraham Geiger's study of the Al-Qur'an and Prophet Muhammad SAW cannot be fully accepted due to his skeptical attitude and negative stigma towards Islam.